New creation in Paul's letters and thought - Hubbard, Moyer V. (Cambridge, UK ; New York : Cambridge University Press, 2002)
As a biblical motif, 'new creation' resonates throughout the pages of the Jewish and Christian Scriptures, and occupies a central place in the apostle Paul's vision of the Christian life. Yet the biblical and extra-biblical occurrences of this theme vary widely in meaning, referring to either a new cosmos, a new community, or a new individual. Beginning with the Old Testament and working through the important texts of Second Temple Judaism, Moyer V. Hubbard focuses on how the motif functions in the argument, strategy, and literary structure of these documents, highlighting its role as the solution to the perceived plight. He then explores in detail which senses of the term Paul intends in Galatians 6.15 and 2 Corinthians 5.17, concluding that 'new creation' in Paul's letters describes the Spirit-wrought newness of the person in Christ, and is fundamentally anthropological in orientation.
Introduction: the current debate -- New creation in the Jewish scriptures : an overview -- New creation in apocalyptic Judaism : jubilees -- New creation in Diaspora Judaism : Joseph and Aseneth -- From death to life : insights from cultural anthropology -- Newness of life : Romans 6:1-11 -- Newness of the Spirit : Romans 7:1-6 -- Spirit, newness, life : the Pauline antecedents -- Crucified with Christ : Galatians 2:19-20 -- If anyone be in Christ : 2 Corinthians 5:17 -- Neither circumcision nor uncircumcision : Galatians 6:15 -- Summary and conclusions.
Originally presented as the author's thesis (doctoral)--University of Oxford, 1998.
Includes bibliographical references (pages 242-267) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Bible. -- Theology; Bible. -- Theology; Bible -- Critique, interprétation, etc; Bible -- Critique, interprétation, etc; Bible. -- Théologie.; Bible; Bible; Paulus -- Apostel, Heiliger; Theological anthropology -- Biblical teaching; Creation -- Biblical teaching; Création -- Enseignement biblique; Anthropologie théologique -- Enseignement biblique; RELIGION -- Biblical Studies -- New Testament; RELIGION -- Biblical Studies -- Paul's Letters; Creation -- Biblical teaching; Theological anthropology -- Biblical teaching; Theology; Neuschöpfung; Electronic books; Electronic books